2012
DOI: 10.5530/pj.2012.33.6
|View full text |Cite
|
Sign up to set email alerts
|

In vitro activity of some medicinal plants from Cachar district, Assam (India) against Candida albicans

Abstract: Introduction: The current research has focused on the potentiality of medicinal plants for treatment of Candida albicans infections. Five plants viz. Clerodendron colebrookianum Walp. (Leaf), Gnetum gnemon L. (Leaf), Sarcochlamys pulcherrima (Roxb.) Gaud. (Leaf), Garcinia lancifolia (Don) Roxb (Leaf) and Euryale ferox Salisb. (Seed), used as traditional medicines in Cachar district, Assam, India were selected to evaluate in vitro activity against C. albicans. Methods: The plant samples were extracted with meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
2
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 25 publications
1
2
0
Order By: Relevance
“…It can be inferred that antimicrobial compounds are present mostly in ethyl acetate and n-butanol fractions, which might be medium polar to polar in nature. Similar obser -vations were also reported earlier in other medicinal plants (Teke et al, 2011;Das et al, 2010;Mazumder et al, 2012). Earlier in a study, higher range of antidermatophytic activity of hexane fraction of O. gratissimum leaves was reported (Silva et al, 2005).…”
Section: Resultssupporting
confidence: 87%
“…It can be inferred that antimicrobial compounds are present mostly in ethyl acetate and n-butanol fractions, which might be medium polar to polar in nature. Similar obser -vations were also reported earlier in other medicinal plants (Teke et al, 2011;Das et al, 2010;Mazumder et al, 2012). Earlier in a study, higher range of antidermatophytic activity of hexane fraction of O. gratissimum leaves was reported (Silva et al, 2005).…”
Section: Resultssupporting
confidence: 87%
“…Previous studies have reported the antioxidant and antifungal properties of S. pulcherrima methanolic extract against C. albicans (Paul et al, 2010 ; Mazumder et al, 2012 ; Mazumder et al, 2014 ). However, the modes of action and efficacy of the extract against multidrug Candida spp.…”
Section: Discussionmentioning
confidence: 99%
“…In a subsequent study, we observed the potential activity of methanolic leaf extracts from S. pulcherrima in the inhibition of Candida albicans . [ 11 ]…”
Section: Biological Activitymentioning
confidence: 99%
“…S. pulcherrima is commonly known as dogal tree (English). It is known by different vernacular names among different tribes and communities, such as Mechaki/Mesaki/Meshangi (Assamese),[ 5 7 8 ] Ombe (Mising),[ 9 ] Ambe (Mishing), Adumbra (Bodo),[ 7 ] Notke (Mishing),[ 10 ] Khajathshear (Khasi),[ 11 ] and Mechaki (Garo). [ 6 ] In Bandarban district of Bangladesh, the plant is known as Ma Cha Da (Marma tribe), Kan Leng (Murang tribe), Jung Gallya sak (Tanchangya tribe),[ 12 ] and Jangaillya shak (Chakma tribe, Hill tract district, Bangladesh).…”
Section: Introductionmentioning
confidence: 99%